Rectal Culture and Sensitivity Analysis for Reducing Sepsis Risk After Fiducial Marker Placement. (December 2018) - Mendenhall, William M.; Sarto, Gail; Bryant, Curtis M.; Morris, Christopher G.; Williams, Christopher R.; Costa, Joseph A.; Bandyk, Mark; Hoppe, Bradford S.; Henderson, Randal H.; Nichols, R. Charles; Mendenhall, Nancy P.
Abstract : Purpose: Placement of fiducial markers for prostate radiotherapy (RT) is associated with a 2% to 3% risk of bacterial urinary tract infection (UTI) that may progress to sepsis necessitating hospitalization. These bacterial UTIs are primarily due to flouroquinolone (FQ) resistant Escherichia coli ( E. coli ). The incidence of this complication has increased in recent years. The purpose of this study is to determine whether rectal culture and sensitivity (C&S) to identify FQ resistant E. coli obtained before placement of fiducial markers for prostate RT reduces the likelihood of this complication. Methods: In total, 412 patients treated with RT at the University of Florida Proton Therapy Institute between 2015 and 2017 were included in the study. Rectal C&S were obtained at the time of initial consultation which preceded placement of fiducial markers for planning and realignment for prostate RT. Patients in whom resistant E. coli were identified had their prophylactic antibiotic regimen modified accordingly. Whether bacterial UTI requiring hospitalization following fiducial placement occurred was prospectively recorded in the medical record on the first day of RT. Results: One of 412 patients (0.2%) developed bacterial sepsis requiring hospitalization after fiducial placement. Conclusion: Rectal C&S to identify FQ resistant E. coli before placement of fiducial markers for prostate RT likely reduces the risk of bacterial UTI necessitating hospitalization.